Peripheral TIGIT+ T Follicular Helper Cells That Produce High Levels of Interleukin-21 via OX40 Represent Disease Activity in IgG4-Related Disease - Akiyama, Mitsuhiro; Suzuki, Katsuya; Yoshimoto, Keiko; Yasuoka, Hidekata; Kaneko, Yuko; Takeuchi, Tsutomu (Frontiers in Immunology, 2021)
Objectives: Multiple studies suggest that interleukin (IL)-21 plays a pivotal role in the differentiation of B cells and activation of cytotoxic T cells and is involved in the pathogenesis of IgG4-related disease (IgG4-RD). T cell immunoreceptor with immunoglobulin and ITIM domain (TIGIT) is a new marker of T follicular helper (Tfh) cells, yet its significance remains unknown. The objective of this study was to investigate whether TIGIT expression could detect high IL-21-producing peripheral Tfh populations and their association with disease activity in IgG4-RD. Methods: TIGIT expression in peripheral CD4+T cell subsets was comprehensively analyzed by multi-color flow cytometry. Single cell mapping was performed by t-SNE method, and IL-21 production was compared in TIGIT+ and TIGIT-T cells. The effect of OX40 signal on cytokine expression was analyzed by RNA-sequencing. Clinical significance of TIGIT+ and TIGIT- peripheral T cells was analyzed in active patients with IgG4-RD, both at baseline and after 12 weeks of glucocorticoid treatment. Results: Unbiased single cell mapping revealed two high IL-21-producing peripheral T cell populations; TIGIT+ Tfh and TIGIT-T helper cells. OX40 signal was associated with high IL-21 production in TIGIT+ Tfh and TIGIT-T helper cells. IL-21 production in Tfh cells correlated with the proportion of TIGIT+ cells in Tfh cells, serum IgG4 level, and scores of disease activity. Furthermore, the skewing toward peripheral TIGIT+ Tfh cells, particularly TIGIT+Tfh2 subset correlated with disease activity and was corrected by glucocorticoid treatment in IgG4-RD. Conclusions: OX40 is associated with high IL-21 production in peripheral TIGIT+ Tfh cells, and the increase in peripheral TIGIT+ Tfh cells reflects disease activity in IgG4-RD.